The nucleobase analog 4-thiouracil hijacks the pyrimidine salvage pathway to inhibit Staphylococcus aureus growth - Matthew J. Munneke; Jeffrey A. Freiberg; Eric P. Skaar (Microbiology Spectrum, 2025)
ABSTRACT Staphylococcus aureus is a leading cause of bacterial-induced mortality due to infections that are increasingly resistant to antibiotics, highlighting the need for new therapeutic strategies to treat these drug-resistant infections. Targeting essential pathways that differ from the host, such as cell wall synthesis, has served as an effective approach for antimicrobial drug development. Nucleotides are essential building blocks for nucleic acids and the bacterial cell wall, and we hypothesized that the metabolic pathways required to obtain these molecules may represent promising antimicrobial targets. To investigate if pyrimidine metabolism could be leveraged to inhibit S. aureus growth, we tested the antimicrobial activity of the uracil derivative, 4-thiouracil (4-TU). Growth of laboratory methicillin-susceptible and resistant strains, including a methicillin-resistant clinical isolate, is inhibited by 4-TU. Based on the structural similarity between 4-TU and uracil, we hypothesized that 4-TU hijacks the pyrimidine salvage pathway for incorporation into RNA. High-performance liquid chromatography (HPLC) analysis showed 4-thiouridine (s4U) in RNA isolated from S. aureus treated with 4-TU. Isolation of 4-TU-resistant S. aureus suppressor strains revealed that mutations in uracil phosphoribosyltransferase (Upp), a component of the pyrimidine salvage pathway, confer resistance to 4-TU. HPLC analysis of RNA isolated from an S. aureus upp mutant demonstrated a lack of s4U, suggesting that upp is required for incorporation of 4-TU into RNA. Expression of Clostridioides difficile thiouracil desulfurase in S. aureus, or cotreatment with uracil and 4-TU, alleviates 4-TU toxicity. Collectively, these findings suggest that 4-TU commandeers the pyrimidine salvage pathway to inhibit S. aureus growth.IMPORTANCEStaphylococcus aureus is associated with greater than one million global deaths annually and is capable of infecting every human tissue. The increasing emergence of antibiotic-resistant strains emphasizes the urgent need to develop new therapeutic strategies to treat infections. Nucleoside analogs that disrupt pyrimidine or purine nucleotide metabolism serve as a promising approach for treating drug-resistant infections, as these pathways differ between host and bacteria. Here, we demonstrate that the uracil derivative 4-thiouracil (4-TU) inhibits S. aureus growth by hijacking the pyrimidine salvage pathway, leading to incorporation of 4-TU into RNA. We found that mutations in uracil phosphoribosyltransferase (upp) confer resistance to 4-TU and prevent incorporation into RNA. Expression of a thiouracil desulfurase (tudS) from Clostridioides difficile is sufficient to detoxify 4-TU and diminish 4-TU levels in RNA. Taken together, these results suggest that 4-TU-mediated disruption of pyrimidine metabolism limits S. aureus growth, which may serve as a promising therapeutic target.